(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Objective: The study's objective was to look into and contrast the effect and prevalence of musculoskeletal problems among teenage athletes and non-athletes. The findings may contribute to the development of rehabilitation plans and preventative actions that support musculoskeletal health in both groups, as well as the assessment of possible gender disparities. Study design : A cross-sectional study. Duration and place of study : department of orthopedic mmc mardan from 05-jan 2020 to 05-july 2020 Methods: A total of 385 adolescents with mean age: 18.12± 02.22 years including 217 athletes with mean age: 19.44±01.38 years and 168 non-athlete controls mean age: 16.80 ± 01.22 were recruited for this study. Anthropometric information was taken and was examined for musculoskeletal symptoms developed over the 06-month duration using Teen Nordic Musculoskeletal Screening Questionnaire (TNMQ-S). The assessment of symptoms and the level of control of school absenteeism and physical activity was compared in the two groups. Results: A higher number of non-athlete controls reported the development of symptoms in the neck (n-171 (45.2%) compared to 93 (24.8%), upper back (157 (42.2%) compared to 75 (20.8%), and low back (161 (43.2%) compared to 131 (34.8%). B. These areas have demonstrated greater rates of physical activity and lower rate of absence from school in athletes as compared to the non-athlete group. C. Among non-athletes, there was a greater development of shoulder 138(37.1%) vs. 101(27.2%) and wrist/hand 79(23.8%) vs. 57(15.2%) symptoms. In the elbow it was 35(9.2%) vs. 36(10.2%), more prevalent in athlete group. Conclusion This study demonstrates the differences between teenage athletes and non-athletes in the occurrence of musculoskeletal symptoms and their effects on physical activity and school attendance. The incidence of symptoms was greater in non-athlete controls, especially in the neck, upper back, and low back areas. This highlights the necessity of focused preventative and rehabilitative treatments in this population.